Optimization in motion planning for parallel robots passing through singular positions - ÖZDEMİR, MUSTAFA (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2017)
Compared to serial robots, parallel robots have many advantages. For this reason, they are used in a wide area, from manufacturing to surgery. However, due to their Type 2 singularities, their workspace is small. As a solution to this problem, consistent motion planning has been proposed in the literature. In this manner a parallel robot can smoothly pass through singular positions, and the whole workspace can be utilized. But the biggest disadvantage of this method is that it can result in back-and-forth motion of the robot end-point along its trajectory. This is a totally undesirable situation from an efficiency perspective. In this article, a theorem is developed and proven to avoid the said problem. Thus, more efficient and effective use of parallel robots is enabled by optimizing the consistent motion planning method.
Keywords: Parallel robot; motion planning; singularity; optimization; CLOSED-LOOP MECHANISMS; INVERSE DYNAMICS; MANIPULATORS; DESIGN; TRACKING